SAE Technical Paper Series 2008
DOI: 10.4271/2008-01-2383
|View full text |Cite
|
Sign up to set email alerts
|

Deposit Formation in the Holes of Diesel Injector Nozzles: A Critical Review

Abstract: Current developments in fuels and emissions regulations are resulting in increasingly severe operating environment for the injection system. Formation of deposits within the holes of the injector nozzle or on the outside of the injector tip may have an adverse effect on overall system performance. This paper provides a critical review of the current understanding of the main factors affecting deposit formation.Two main types of engine test cycles, which attempt to simulate field conditions, are described in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 40 publications
0
48
0
1
Order By: Relevance
“…Shifts towards piezo-actuated injectors mean that dynamic response times are improved, reducing the time spent in the transient injection phase. This has been shown to give superior fuel air mixing when compared with older systems using solenoid actuated injectors [5,6]. A more recent technique in injection optimisation utilises split injection strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shifts towards piezo-actuated injectors mean that dynamic response times are improved, reducing the time spent in the transient injection phase. This has been shown to give superior fuel air mixing when compared with older systems using solenoid actuated injectors [5,6]. A more recent technique in injection optimisation utilises split injection strategies.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in performance is known to manifest in a variety of ways including increased acoustic and pollutant emissions [1][2][3]. The deposits can also reduce the hydraulic diameter of the nozzle hole, resulting in a reduction in the quantity of injected fuel and reduced quality and consistency of injection [3][4][5]; all of which cause a reduction in engine power [6]. The deposits can also increase cavitation, which can then lead to further coking of the nozzle [7].…”
Section: Introductionmentioning
confidence: 99%
“…This confirms that the volume of fuel that makes up the spheroidal cap can exist as trapped fuel in the orifice of the nozzle. The possibility of fuel being stored in the injector holes after the end of the injection process has been discussed in [20] and [21], and is believed to contribute to the formation of deposits in the nozzle orifices.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally the high temperatures in the engine, when thermally conducted along the injector, will likely act as an accelerant to deposit formation. It is generally observed that higher engine temperatures increase deposit severity [6,8,9,12].…”
Section: Deposit Morphologymentioning
confidence: 99%